LA IMPLEMENTACIÓN DEL PLAN NACIONAL SEMILLA EN LA ENTREGA DE KITS DE PASTOS EN EL CANTÓN CELICA, AÑO 2022. - Calva Valdiviezo, Jhakson Joel (2024)
Public policies require the active involvement of local and national actors and the general community in order to ensure that their planning and execution truly respond to collective interests. In this sense, this study carried out an exhaustive evaluation about the implementation of the “Plan Nacional Semilla” with the aim of contributing to the improvement of the implementation of pasture kit distribution in the Celica canton during 2022. To this end, the specific objectives were; to evaluate the deficiencies identified in the implementation of the “Plan Nacional Semilla” in the Celica canton and, to design an action plan that effectively addresses the deficiencies identified in its execution. The methodology was qualitative using an exploratory-descriptive approach with the purpose of conducting a detailed document revision and applying interviews in order to gather valuable and specific perspectives regarding the process. The results revealed that there was a significant distribution of 126 technological kits to 73 livestock farmers in Celica: San Juan de Pózul parish experienced a wide coverage, while Cruzpamba and the cantonal center had a more limited presence due to the lack of extensive livestock areas. A large number of small and medium-scale farmers were beneficiaries of the plan launched by the Ministerio de Agricultura y Ganadería, however, there was certainly resistance from some farmers who showed a certain rejection of technification and preferred to maintain traditional practices.